Middle East and North Africa Registry to Characterize Rate of RAS Testing Status in Newly Diagnosed Patients with Metastatic Colorectal Cancer - Oukkal, Mohammed; Bouzid, Kamel; Bounedjar, Adda; Alnajar, Abdulsalam; Taleb, Fouad Abou; Alsharm, Abdullah; Mahfouf, Hassen; Larbaoui, Blaha; Abdelaziz, Amr; Ouamer, Assia; et al. (Turkish Journal of Gastroenterology, 2022)
Background: Rat sarcoma virus mutational status guides first-line treatment in metastatic colorectal cancer. This study was a multicenter, multi-country ambispective, observational study in the Middle East and North Africa assessing regional rat sarcoma virus testing practices in newly diagnosed patients. Methods: The retrospective arm (2011-2014) included adults with metastatic colorectal cancer who had initiated first-line therapy with ≥1 post-baseline visit and survival data. The prospective arm (2014-2019) enrolled newly diagnosed patients with histologically proven metastatic colorectal cancer with ≥1 measurable lesion per Response Evaluation Criteria in Solid Tumors, and tissue availability for biomarker analysis. Data look-back and follow-up were 2 years; the rate of RAS mutation was evaluated. Results: RAS testing was ordered for patients in retrospective (326/417) and prospective (407/500) studies. In the former, testing was typically prescribed after first-line treatment initiation, significantly more in patients with stage IV disease (P < .005), resulting in the addition of targeted therapy (41.8% anti-epidermal growth factor receptor, 30.2% anti-vascular endothelial growth factor) in wild-type metastatic colorectal cancer, and significantly impacted the treatment of left-sided tumors (P = .037). In the latter, 58.4% were RAS wild-type; 41.6% were RAS mutant. Non-prescription of RAS testing was attributed to test unavailability, financial, or medical reasons; predictors of testing prescription were older age, primary tumor in ascending colon, and high tumor grade. RAS status knowledge resulted in the addition of anti-vascular endothelial growth factor (20.4%) or anti-epidermal growth factor receptor therapy (21.2%). Conclusion: Before 2014, RAS testing in patients with colorectal cancer in the Middle East and North Africa was often performed after first-line treatment. Testing is more routine in newly diagnosed patients, potentially shifting early treatment patterns Cite this article as: Oukkal M, Bouzid K, Bounedjar A, et al. Middle East and North Africa registry to characterize rate of RAS testing status in newly diagnosed patients with metastatic colorectal cancer. Turk J Gastroenterol. 2023;34(2):118-127.